Functional Optimization of Smart Street Lamp via Hybrid Kano-DEMATEL Model: A Case Study on Hebi Area, China - Ge, Junchao (International Journal of Integrated Engineering, 2024)
World’s major cities are rapidly advancing towards the development of smart cities. Smart street lamps, due to their integration and systematization, have become the most promising physical infrastructure for realizing smart city construction. However, current smart street lamps face obstacles such as functional redundancy, arbitrary design, and neglect of urban residents’ emotional needs, with the function setting of smart street lamps being a prominent challenge. Research how to optimize function settings to enhance cost-effectiveness and practicality is crucial. However, existing research in this area is limited, lacks systematic and quantitative analysis methods, and does not explore the complexity and interrelationships between functional integration adequately. Consequently, it fails to address the issues of avoiding redundant and mismatched functional settings of smart street lamps. This paper proposes a novel approach that leverages the strengths of the Kano model and the DEMATEL method, culminating in the establishment of a hybrid Kano-DEMATEL Model for comprehensively ranking smart street lamp functions. The model comprises four layers: the target layer, the Kano criterion layer, the DEMATEL criterion layer, and the requirements sorting table layer. The ordering strategy involves using the Kano model as the primary criterion and complementing it with the DEMATEL method as the secondary criterion. This model brings clarity to the importance of optimizing various indicators, provides a clearer understanding of the strengths and weaknesses of product functions, and considers correlations and complementarities between different functions, ultimately enhancing the cost-effectiveness and practicality of smart street lamps. By applying this model, this paper obtained a thorough ranking of the 21 must-be, expected, and attractive functions of smart street lamps. Furthermore, aligning these findings with specific regional research requirement, the functions of new smart street lamps were successfully optimized in the Hebi area, leading to substantial improvements and successful construction outcomes.